Cognitive underpinnings and ecological correlates of implicit bias against non-Americans in the United States - Benedek Kurdi; Keitaro Okura; Eric Hehman; Melissa J. Ferguson (Scientific Reports)
Abstract Of the 330 million residents of the United States, over 40 million were born abroad. Such individuals are routinely referred to using labels such as “alien,” “foreigner,” and “noncitizen.” In this multimethod project relying on data from 5437 U.S. citizens in experimental studies and 193,649 U.S. citizens in archival studies, we examine implicit (automatic) evaluations of non-Americans in the United States, their effects on impression formation, and their ecological correlates in the form of real-life outcomes. In Studies 1A–1C, the labels “alien,” “foreigner,” and “noncitizen” were found to be highly and similarly implicitly negative. In Studies 2A–2D, applying these labels to specific individuals created immediate implicit negativity toward them, irrespective of their gender or race. Finally, pro-American/anti-foreigner implicit evaluations predicted anti-immigrant policy positions at the level of individuals (Study 3A), and a conceptually and statistically related implicit White–American/Asian–foreign implicit stereotype predicted anti-immigrant voting patterns in 18 relevant ballot initiatives at the level of U.S. counties (Study 3B). Across studies, implicit anti-foreigner bias generalized across participant demographics but was somewhat stronger among men and political conservatives. Together, this work highlights the cognitive underpinnings and real-world correlates of robust and pervasive anti-foreigner biases in the United States.